Chaetomitrium Roemeri - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are small, densely and pinnately to bipinnately branched, forming compact mats, (2) stem leaves are erect-spreading to recurved, sub-orbicular with abruptly acuminate apices, and plane or slightly constricted below apices; (3) leaf margins are slightly recurved near the base, denticulate with simple teeth; (4) lamina cells are coarsely spinose-prorate abaxially especially below apex, prorate below; (5) alar cells are sub-rectangular.